Potential for natural hydrogen in Quebec (Canada): a first review - Séjourné, Stephan; Comeau, Félix-Antoine; Moreira dos Santos, Maria Luisa; Bordeleau, Geneviève; Claprood, Maxime; Mouge, Pascal; Mulliez, Valentin; Malo, Michel; Giroux, Bernard; Gloaguen, Erwan; Raymond, Jasmin (Frontiers in Geochemistry, 2024)
The energy transition calls for natural hydrogen exploration, with most occurrences discovered either inadvertently or, more recently, at the location of potentially through the detailed study of diffusive circles identified observed from a change of vegetation cover at the surfacein the field or by satellite imagery. However, some notable hydrogen occurrences are not directly associated with the presence of diffusive circles with the typical case beinglike the Bourakebougou field in Mali. Thus, the objective of this work was to highlight geological areas that have some potential to find natural hydrogen in Quebec, a Canadian province where no diffusive circles have yet been documented but which is rich in potential source rocks and where no exploration for natural hydrogen has been undertaken so far. A review of the different geological regions of Quebec was undertaken to highlight the relevant characteristics and geographical distribution of geological assemblages that may produce or have produced natural hydrogen, in particular, iron-rich rocks but also uranium-rich rocks, supramature shales and zones where significant structural discontinuities are documented or suspected, which may act as conduits for the migration of fluids of mantle origin. In addition to regional and local geological data, an inventory of available geochemical data is also carried out to identify potential tracers or proxies to facilitate subsequent exploration efforts. A rating was then proposed based on the quality of the potential source rocks, which also considers the presence of reservoir rocks and the proximity to end-users. This analysis allowed rating areas of interest for which fieldwork can be considered, thus minimizing the exploratory risks and investments required to develop this resource. The size of the study area (over 1.5 million km 2 ), the diversity of its geological environments (from metamorphic cratons to sedimentary basins) and their wide age range (from Archean to Paleozoic) make Quebec a promising territory for natural hydrogen exploration and to test the systematic rating method proposed here.